Underrepresenting Reality? Media Coverage of Women in Politics and Sport. (7th July 2020) - Courtney, Michael; Breen, Michael; McGing, Claire; McMenamin, Iain; O'Malley, Eoin; Rafter, Kevin
Abstract : Objectives: How do surges in female representation in public life affect media coverage? Can the media underrepresent the reality of women's progress? If so, is the source of underrepresentation the media itself or social elites that interact with the media? Methods: Using automatic content analysis, we study two remarkable step changes in women's role in public life in Ireland: the 2016 elections and 2012 Olympics. Results: The increase in female participation was associated with a new and substantial gender gap in coverage, which we attribute to the media, not other elites. Conclusions: We cannot assume that media coverage will increase proportionally as women advance in public life. The reemergence of bias when female representation jumps may also exist outside the media in any context where there are large numbers of decisions about whether to favor males or females.